The granulocyte colony-stimulating factor (G-CSF) upregulates metalloproteinase-2 and VEGF through PI3K/Akt and Erk1/2 activation in human trophoblast Swan 71 cells - Furmento, Verónica Alejandra (2014)
INTRODUCTION: Although the expression of the granulocyte colony-stimulating factor (G-CSF) and its receptor (G-CSFR) in placental tissues suggests that the cytokine could play a role in placental development, the relevance of G-CSF:G-CSFR interaction in trophoblast cells remains to be studied. Thus, the possible functional role of G-CSF was examined in a human trophoblast cell line (Swan 71 cells). METHODS AND RESULTS: The expression of G-CSFR was detected by immunocytochemistry and Western blot assays. G-CSF treatment exerted neither a proliferative nor a protective effect on H2O2-mediated cell death in trophoblast cells. Gelatin zymography of supernatants collected from G-CSF-treated cells showed an increment of metalloproteinase-2 (MMP-2) activity. We also found higher MMP-2 and VEGF expression levels in conditioned medium from cells exposed to G-CSF. In addition, it was demonstrated that G-CSF induced the activation of PI3K/Akt and Erk1/2 pathways, which in turn activated NF-kB. By using selective pharmacological inhibitors, it was showed that these pathways are mediating the biological effects produced by G-CSF in Swan 71 cells. DISCUSSION AND CONCLUSION: We have demonstrated for the first time that G-CSF increases MMP-2 activity and VEGF secretion in Swan 71 cells through activation of PI3K/Akt and Erk signaling pathways, both contributing to the translocation of NF-kB to the nucleus. These data suggest that G-CSF is involved in the regulation of trophoblast function, and should be considered as a locally produced cytokine probably contributing to embryo implantation and the development of a functional placenta.